AERONET data investigation of the aerosol mixtures over Iasi area, One-year time scale overview. (March 2015) - Cazacu, Mihai Marius; Timofte, Adrian; Unga, Florin; Albina, Bogdan; Gurlui, Silviu
Abstract: In order to analyze the troposphere dynamics under particular conditions in North-East region of Romania, various types of aerosols chemical compositions have been studied using complementary techniques. Thus, the seasonal trends of aerosols and its external influences have been studied using aerosol optical properties retrieved from Aerosol Robotic Network (AERONET). Complementary studies were taken into account by using several meteorological factors, computational models and meteorological data. Moreover, this paper presents optical properties analysis of different types of aerosols and the seasonal variability of them in one year of measurements. The major categories of aerosol types are evidenced, such as urban/industrial aerosol, biomass burning and mineral dust. Highlights: One year AERONET data of sunphotometer measurements were analyzed. The seasonal trends of aerosols and its external influences have been studied. Urban/industrial aerosols have a strong influence over entire aerosols load. Complementary studies to observe the impact of Saharan dust over water vapors.